Analysis of oil production by applying in situ combustion. (2nd January 2016) - Araújo, E. A.; Diniz, A. A. R.; Gurgel, A. R.; Lima, D. M. B. S.; Dutra, T. V.; Barillas, J. L. M.
ABSTRACT: The THAI (toe-to-heel air injection) process is a process of enhanced oil recovery, which consists of integrating the in situ combustion process with technological advances of horizontal wells drilling, and has not yet been applied in Brazil. Motivated by this context, the authors aimed to studying the application of the THAI process in a semisynthetic reservoir, with characteristics similar to those ones found in the Brazilian Northeast. It was analyzed the air injection rate, indicating that there is a limit to reach a good efficiency.